2023
DOI: 10.1055/s-0043-1768662
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios and prognosis after aneurysmal subarachnoid hemorrhage: a cohort study

Abstract: Background Subarachnoid hemorrhage (SAH) prognosis remains poor. Vasospasm mechanism might be associated with inflammation. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been studied as inflammation markers and prognostic predictors. Objective We aimed to investigate NLR and PLR in admission as predictors of angiographic vasospasm and functional outcome at 6 months. Methods This cohort study included consecutive aneurysmal SAH patients admitted to a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Several previous studies have demonstrated the association of NLR with unfavorable functional outcomes in AIS (Chen et al., 2020 ), acute intracerebral ICH (Zhang et al., 2023 ), and subarachnoid hemorrhage (Oliveira & Rabelo, 2023 ). It has been reported that high neutrophil counts have been found at various stages of atherosclerosis, which could damage endothelial cells (Feng et al., 2023 ).…”
Section: Disscusionmentioning
confidence: 94%
“…Several previous studies have demonstrated the association of NLR with unfavorable functional outcomes in AIS (Chen et al., 2020 ), acute intracerebral ICH (Zhang et al., 2023 ), and subarachnoid hemorrhage (Oliveira & Rabelo, 2023 ). It has been reported that high neutrophil counts have been found at various stages of atherosclerosis, which could damage endothelial cells (Feng et al., 2023 ).…”
Section: Disscusionmentioning
confidence: 94%